PENGARUH KINERJA KEUANGAN, UKURAN PERUSAHAAN, DAN RISIKO BISNIS TERHADAP STRUKTUR MODAL - Amiriyah, Amiriyah (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to examine the influence of financial performance (which is proxy with salesgrowth and profitability), company size and business risks to the capital structure. The result of the researchshows that this research regressions model has fulfilled the BLUE (Best Linear Unbiased Estimator)requirements that there is no heteroscedasticiy, multicolinearity, and autocorrelation symptoms and the data isnormally distributed. The result of multiple regression analysis shows that profitability has significant influenceto the capital structure; sales growth has significant influence to the capital structure; company size has nosignificant influence to the capital structure and business risks have no significant influence to the capitalstructure.Keywords: Profitability, Sales Growth, Company Size, Business Risks, Capital Structure.